GEOGRID ANALYSIS OF SOIL SHEAR STRENGTH - Nasution , Mahliza (International Conference on Health Science, Green Economics, Educational Review and Technology, 2022)
Improving soil conditions is one solution to the problem of increasing soil carrying capacity and minimizing settlement. With the development of technology in the geotechnical field, soil strengthening can be done by installing synthetic materials such as the use of geogrids. Geogrids rely on high tensile strength and low creep elongation, for the case of landslides geogrids are placed on a layer of soil, backfilled, and compacted layer by layer so as to maintain stabilizing soil by distributing it to be strong. Tensile purpose of this study To describe the use of geogrids in their role as one of retaining wall reinforcement. In planning, the retaining wall must be able to withstand the loads acting on it, both externally and internally. , shear and slip bearing capacity, and settlement. Internally stability indicates the stability of the type of reinforcement itself, in this case such as tensile capacity, friction capacity, bending capacity.